Distribution of DNase I-sensitive sites in simian virus 40 nucleoprotein complexes from disrupted virus particles. - Hartmann, J P (1981)
Nucleoprotein complexes (core particles) released from simian virus 40 (SV40) virions were compared with similar complexes (SV40 chromatin) extracted from nuclei of infected cells. Core particles were sensitive to cleavage by DNase I at about the same enzyme concentration required to cleave SV40 chromatin. DNase I preferentially cleaved SV40 chromatin adjacent to the viral origin of replication; however, cleavage of core particles occurred with much less selectivity. The difference between these nucleoproteins was not due to a structural alteration induced by the virion disruption procedure, since SV40 chromatin retained its pattern of DNase I-sensitive sites when subjected top this treatment. On the other hand, core particles did not acquire the nuclease-sensitive feature typical of SV40 chromatin when they were exposed to infected cell nuclei and the Triton X-100-EDTA extraction procedure. Hence, the nuclease-sensitive feature was lost or altered during the normal process of virion assembly and maturation.